Little mercies - Gudenkauf, Heather (Park Row Books, 2024)
"Veteran social worker Ellen Moore is a fiercely dedicated children's advocate and a devoted mother and wife. But one blistering summer day, a simple moment of distraction will have repercussions that Ellen could never have imagined. Meanwhile, ten-year-old Jenny Briard suddenly finds herself on her own, forced to survive with nothing but a few dollars and her street smarts. The last thing she wants is a social worker, but when Ellen's and Jenny's paths collide, little do they know just how much they will change each other's life."--